2017
DOI: 10.1113/jp274795
|View full text |Cite
|
Sign up to set email alerts
|

Subunit‐dependent oxidative stress sensitivity of LRRC8 volume‐regulated anion channels

Abstract: The volume-regulated anion channel (VRAC) is formed by heteromers of LRRC8 proteins containing the essential LRRC8A subunit and at least one among the LRRC8B-E subunits. Reactive oxygen species (ROS) play physiological and pathophysiological roles and VRAC channels are highly ROS sensitive. However, it is unclear if ROS act directly on the channels or on molecules involved in the activation pathway. We used fluorescently tagged LRRC8 proteins that yield large constitutive currents to test direct effects of oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 46 publications
2
73
0
Order By: Relevance
“…Second, when Xenopus oocytes, which virtually lack all LRRC8 genes and endogenous VSOR activity, were coinjected with LRRC8A with 8B or that of Volume-Activated and Volume-Correlated Anion Channels LRRC8A tagged with fluorescent proteins (8A*) and 8B*, hypotonic stimulation failed to activate VSOR currents, although coinjection of LRRC8A plus 8E/8D or of 8A* plus 8C*/8D*/8E* produced VSOR activity (Gaitán-Peñas et al, 2016). In addition, VSOR activity was not induced by coinjection of 8A* with 8B* even after application of a membrane-permeable oxidizing agent, whereas VSOR currents induced by coinjection of 8A* plus 8C*/8D*/8E* were, in contrast, greatly affected by oxidation (Gradogna et al, 2017). Third, triple knockdown of LRRC8C, 8D, and 8E abolished endogenous VSOR activity in HeLa cells, which endogenously express all five LRRC8 genes (Sato-Numata et al, 2017).…”
Section: B Volume-sensitive Outwardly Rectifying Anion Channelmentioning
confidence: 89%
See 1 more Smart Citation
“…Second, when Xenopus oocytes, which virtually lack all LRRC8 genes and endogenous VSOR activity, were coinjected with LRRC8A with 8B or that of Volume-Activated and Volume-Correlated Anion Channels LRRC8A tagged with fluorescent proteins (8A*) and 8B*, hypotonic stimulation failed to activate VSOR currents, although coinjection of LRRC8A plus 8E/8D or of 8A* plus 8C*/8D*/8E* produced VSOR activity (Gaitán-Peñas et al, 2016). In addition, VSOR activity was not induced by coinjection of 8A* with 8B* even after application of a membrane-permeable oxidizing agent, whereas VSOR currents induced by coinjection of 8A* plus 8C*/8D*/8E* were, in contrast, greatly affected by oxidation (Gradogna et al, 2017). Third, triple knockdown of LRRC8C, 8D, and 8E abolished endogenous VSOR activity in HeLa cells, which endogenously express all five LRRC8 genes (Sato-Numata et al, 2017).…”
Section: B Volume-sensitive Outwardly Rectifying Anion Channelmentioning
confidence: 89%
“…Since membrane unfolding-and oxidation-induced activation was shown to be additive under certain conditions (Gradogna et al, 2017), type A and type B mechanisms would be independent of each other. When cells respond to hypo-osmotic stress not only with osmotic cell swelling but also with ATP release, VSOR activation can dually be attained by the Ca 2+ -independent, membrane unfolding-induced type A mechanism and by the Ca 2+ nanodomain-dependent, oxidationinduced type B mechanism ( Fig.…”
Section: B Volume-sensitive Outwardly Rectifying Anion Channelmentioning
confidence: 99%
“…Anion channels are implicated in sperm volume regulation, of which the molecular identity remains poorly understood due to the lack of channel-specific blockers. The recent discovery of LRRC8A as an obligatory subunit of VRAC has invoked extensive follow-up studies, demonstrating multiple functions of LRRC8A-dependent VRAC pathway (5,7,18,20,23,24). However, these studies have mostly been performed in immortalized cell lines, in which cells were stressed with large hypotonic imbalances.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 2 groups independently identified LRRC8 heteromers as the pore-forming subunits of the long-sought VRAC (18,19). In particular, the LRRC8A protein (also known as SWELL1) was validated as the obligatory component of the VRAC (6,18,19) and functions in conjugation with at least 1 other LRRC8 family member in a tissue-specific manner (5,20,21). Subsequent studies, mostly performed in cultured cell lines, showed that LRRC8Adependent VRAC activity is involved in a broad range of biological processes, including cell proliferation, migration, apoptosis, and insulin secretion and uptake, in addition to volume regulation (5,(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of The Journal of Physiology , Gradogna et al . () shed light on the modulation of VRAC current by oxidation. They show opposite effects depending on the different combinations of LRRC8 subunits.…”
Section: Regulation By Oxidation Of the Volume‐regulated Anion Channementioning
confidence: 99%